Effects of blood flow restriction during moderate-intensity eccentric knee extensions - Behringer, Michael; Heinke, Lars; Leyendecker, Jannik; Mester, Joachim (The journal of physiological sciences, 2018)
We investigated if blood flow restriction (BFR, cuff pressure 20 mmHG below individual occlusion pressure) increases metabolic stress, hormonal response, release of muscle damage markers, and muscle swelling induced by moderate-intensity eccentric contractions. In a randomized, matched-pair design, 20 male subjects (25.3±3.3 years) performed four sets of unilateral eccentric knee extensions (75% 1RM) to volitional failure with (IG) or without (CG) femoral BFR. Despite significant differences of performed repetitions between IG (85.6±15.4 repetitions) and CG (142.3±44.1 repetitions), peak values of lactate (IG 7.0±1.4 mmol l−1, CG 6.9±2.7 mmol l−1), growth-hormone (IG 4.9±4.8 ng ml−1, CG 5.2±3.5 ng ml−1), insulin-like growth factor 1 (IG 172.1±41.9 ng ml−1, CG 178.7±82.1 ng ml−1), creatine-kinase (IG 625.5±464.8 U l−1, CG 510.7±443.5 U l−1), the absolute neutrophil count (IG 7.9±1.3 103 µl−1, CG 8.7±2.0 103 µl−1), induced muscle swelling of rectus femoris and vastus lateralis and perceived pain did not differ. The present data indicate that BFR is suitable to intensify eccentric exercises.